KETEPATAN WAKTU MASUK DAN PULANG KANTOR PEGAWAI NEGERI SIPIL DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KUBU RAYA - Arif Guritno E. 21105046 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
This research aimed to describe civil servants discipline in Population and Civil Registration Agency of Kubu Raya Regency to entry time and home office. The focus of research is entery timeliness and home timeliness office. The type of research is a descriptive study. Research subjects all civil servants of class II and III with the data collection techniques using direct observation techniques and interview techniques. To analyze the data using qualitative techniques. The results of research showed that the civil servants discipline in Population and Civil Registration Agency of Kubu Raya Regency to entri time office are low because there are civil servants do not get in on time or late. Civil servants discipline to home time office is also low because there are civil servants do not return on time. Based on research results the authors suggest that carrying out regular morning assembly though slightly civil servants had come to the office and give severe sanctions for civil servants are often late not only a verbal warning but doubt moving staff and carry out regular daytime assembly and selectively give out licenses means to be out only for official purposes, getting the disaster and ill, remember there are civil servants that came out during office hours did not return to the office. Keywords: entry timeliness, home timeliness